The importance of using accessible social media networks in teach the characteristics of Arabic language for non-native speakers - PSU university Thailand students as a model - Rusdee, Taher; Wilailak, Wisetrat; Prasert, Panprae; Siddiq, Alee; Zainab, Puteh; Yousef A. Baker, El-Ebiary (2020)
The study aimed to reveal the reality of the use of social media networks, and to identify and arrange the most important ones in use, and its most important characteristics affecting Arabic distance education from the viewpoint of students of Prince Songkla University, Fatani Branch, Thailand, and used the descriptive analytical approach, and the questionnaire as a tool to collect data and information, and reached Results, the most important of which are: The reality of the sample's use of communication networks is medium and acceptable, the most important of which is Facebook, the paragraph got from the questionnaire phrases; Which is: (ease of communication with colleagues and friends of study) on the first rank, and this indicates that the degree of impact is very large; This result confirms the importance of the sample members ’attention to academic relations and friendships, and the use of communication networks for their development and strengthening, and recommended strengthening the characteristics of these networks in teaching and investing in Arabic in a way that serves the distance education process, and the necessity of joining efforts of those in the teaching of Arabic to speakers of others globally to direct capabilities towards benefiting from The advantages and characteristics of these networks.